Experimental study on residual properties of carbon fibre reinforced plastic (CFRP) and aluminum single-lap adhesive joints at different strain rates after transverse pre-impact. (September 2019) - Liu, Xinglong; Shao, Xuefei; Li, Qing; Sun, Guangyong
Abstract: The adhesive joints connecting carbon fiber reinforced plastic (CFRP) composites with aluminum alloy (Al5182) could experience multiple impacts at different rates from different directions in service. However, there has been no study available in the open literature concerning the axial residual performances of the CFRP/Al5182 adhesive single-lap joints after low-velocity transverse impact. This study aimed to address this issue through the experiment. Based upon the testing results, the CFRP/Al5182 adhesive joints presented significant rate dependence; and the joints strength showed a rising tendency with increasing strain rate. Meanwhile, by analyzing the macroscopic and microcosmic fracture surfaces it was found that the failure modes for the adhesive joints gradually transformed from the cohesive failure and adhesive failure modes to the cohesive failure and fiber-tear failure modes with increasing strain rate. The joint strength and failure elongation both decreased with increasing transverse pre-impact energy; which were however independent of the axial tensile velocity. For the pre-impacted joints under a higher strain rate, the adhesive in the fracture surface mainly experienced the brittle failure and delamination of CFRP adherends. Finally, the results of two-way analysis of variance (ANOVA) showed that the effects of axial strain rate and transverse pre-impact were the two main factors to affect the residual strength of joints, but the interaction was not strong. Based upon the failure mechanisms, an empirical formula was derived analytically to predict the joint strength after transverse pre-impact under different axial strain rates.